2015
DOI: 10.1158/1078-0432.ccr-15-1362
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Targeting the Stimulator of Interferon Genes (STING) in the Immunotherapy of Cancer

Abstract: Novel immunotherapy approaches are transforming the treatment of cancer, yet many patients remain refractory to these agents. One hypothesis is that immunotherapy fails because of a tumor microenvironment that fails to support recruitment of immune cells including CD8+ T cells. Therefore, new approaches designed to initiate a de novo anti-tumor immune response from within the tumor microenvironment are being pursued. Recent evidence has indicated that spontaneous activation of the Stimulator of Interferon Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 66 publications
(72 reference statements)
4
115
0
Order By: Relevance
“…Indeed, paradoxical responses to oHSV have been reported whereby tumor cells which were characterized as oHSV resistant in vitro were more susceptible to the anti-tumor effect of oHSV in vivo (46). While we have demonstrated associated STAT1 activation to be detrimental to oHSV productivity in vitro , it will be necessary to identify how tumor cells that are STAT1 responsive interact with the peripheral immune elements in this context since the efficacy of certain immunotherapies and the recruitment of CTLs is dependent upon the Type-I IFN response (47). Additionally, the use of powerful immunosuppressants such as JAK inhibitors may counteract the effects of immunotherapy or diminish the safety profiles which have been previously established for oHSV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, paradoxical responses to oHSV have been reported whereby tumor cells which were characterized as oHSV resistant in vitro were more susceptible to the anti-tumor effect of oHSV in vivo (46). While we have demonstrated associated STAT1 activation to be detrimental to oHSV productivity in vitro , it will be necessary to identify how tumor cells that are STAT1 responsive interact with the peripheral immune elements in this context since the efficacy of certain immunotherapies and the recruitment of CTLs is dependent upon the Type-I IFN response (47). Additionally, the use of powerful immunosuppressants such as JAK inhibitors may counteract the effects of immunotherapy or diminish the safety profiles which have been previously established for oHSV.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, sufficient stimulation of innate sensory pathways (such as TLR3-IFNAR stimulation following anthracycline chemotherapy-induced immunogenic cell death [ICD] of tumor cells) can induce type I IFN that in turn stimulates secretion of the chemokine CXCL10 for TIL recruitment to tumor beds (Sistigu et al, 2014). Similarly, in vivo studies have demonstrated an important role for type I IFN production following activation of the stimulator of interferon genes (STING) pathway in the BATF3 lineage of DCs; this role is necessary for optimal T cell recruitment to tumors and spontaneous anti-tumor T cell responses (Corrales and Gajewski, 2015;Deng et al, 2014;Diamond et al, 2011;Fuertes et al, 2011;Woo et al, 2014) and suggests a potential application for STING agonists as cancer therapeutics (Corrales and Gajewski, 2015).…”
Section: Importance Of Type I Ifn Signalingmentioning
confidence: 99%
“…Dying tumor cells release intracellular components such as high-mobility-group box 1, ATP, and DNA, which are recognized, in turn, by receptors such as Toll-like receptor (TLR) 4 (Apetoh et al, 2007), P2X7 receptor (P2X7R) (Ghiringhelli et al, 2009), and stimulator of interferon genes (STING) (Deng et al, 2014) to regulate immune responses against tumors. Accordingly, a number of innate sensor agonists are being brought forward for investigation in cancer patients (Corrales and Gajewski, 2015; Kaczanowska et al, 2013; Rook et al, 2015). …”
Section: Introductionmentioning
confidence: 99%